Information reification: fake news about Covid-19 on the website of the Brazilian Departament of Health - Rodrigo Silva Caxias de Sousa; Patricia Valerim (Liinc em Revista)
This study analyzes fake news published on the website of the Brazilian Department of Health about COVID-19 in 2020. It argues that different forms of disinformation were constituted into reified communicative processes. The study emphasizes the emergence of a disinformation production circuit whose logic is the trivialization of informational practices manifested through fake news. The methodology applied here is of an exploratory-descriptive work with a qualitative approach and content analysis. The analyses prompted the emergence of six categories obtained a posteriori: main theme, language, elements that make up the news, rhetorical devices, devices for attributing credibility to the news, and fact-checking procedures. It can be affirmed that the news articles found are based on instrumental compositions that articulate themes related to the pandemic in a simplistic way, with language that disregards grammar norms, and resorting to the combined use of several elements, specially through text and image, and of different rhetorical devices – with the recurrent use of authorities to attribute credibility to the news, and the presence of inconsistencies in fact-checking procedures by Department of Health. Finally, it can be affirmed that the fact-checking carried out by the Brazilian Department of Health had as reference the politicization of the disease in face of the tension between science, politics and the market, which compromises the fight against this health crisis and corroborates the instrumental logic of the information circulating on the web